EFFECT OF pH AND MANGANESE KATION ON THE ACTIVITY OF COW RUMEN FLUID CELLULASE ENTRAPPED IN CALCIUM ALGINATE BEADS - I. Hartati; L. Kurniasari; I. Riwayati; A. Budiarti (Universitas Wahid Hasyim, 2012)
Enzyme entrapment in calcium alginate beads is considered as one of the important methods of immobilization. In order to utilize cow rumen fluids as source of cellulase and in order to increase the cellulase activity, we were isolated cellulase of cow rumen fluid and investigated the influence of pH (5-9) and concentration of Mn2+ (25-100 mM) towards the activity of the cellulase that is entrapped in calcium alginate beads. The research showed that the immobilization of cow rumen fluid cellulase in alginate beads is lead to a higher optimum pH. Free cellulase exhibit the highest activity at pH 4 while the entrapped cellulase exhibit the highest activity of 145 U/ml at pH 6. Mn2+ is significantly stimulate the activity of entrapped cow rumen fluid cellulase.Keywords: alginate beads, cow rumen fluids cellulase, immobilization, pH, Mn